Analysis of Deliveries Using Robson’s 10-Group Classification at a Semi-Urban Hospital - Chowdhury, Afsana Haque; Ara, Anjuman; Dewan, Farhana; Nessa, Khairun (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Introduction: Cesarean section (CS) is an important indicator of access to, and quality of maternal health services. The World Health Organization recommends the Robson’s ten group classification system. Method: This is a prospective study carried out over a period of one year from Jan 2018 to Dec 2018. All caesarian section conducted during the study period were included in the study. Patients’ demographic data age, parity, gravidity, pregnancy related information- gestational age, fetal presentation, number of fetuses, onset of labor, delivery details operative or vaginal delivery, indications of Caesarian section, type of C-section, fetal details - APGAR scores, all were recorded. Based on patients’ data, women were assigned to one of 10 groups as per Robson’s 10-group classification system. This classification system categorizes women into ten mutually exclusive groups, considering the following criteria: parity, previous obstetric record of the woman, the course of labor including pre-labor duration and gestational age. Result: Overall Caesarean section rate of 42%. Total number of deliveries in this one-year period was 1727 of which 715 women had lower segment caesarean section (41.4%). Group 5 contributed the most (19%) followed by Group 1 (6.5%) then Group 2(5.6%). Women in group 2(b)& 4(b) went into had a CS rate around 6.7%. Conclusions: Robson 10 group classification is an important tool to classify the indication of caesarian section. Implementation of this classification system may help in reducing primary caesarian section as well as caesarian section done for relative indications & encourage VBAC without compromising health of mother & newborn. Bangladesh J Obstet Gynaecol, 2023; Vol. 38(1): 27-34